An analytical model for predicting specific cutting energy in whirling milling process. (10th December 2019) - He, Yan; Wang, Lexiang; Wang, Yulin; Li, Yufeng; Wang, Shilong; Wang, Yan; Liu, Chao; Hao, Chuanpeng
Abstract: The specific cutting energy (SCE) of machining processes is a significant indicator for machining sustainability. However, the characteristics of SCE in whirling milling as a promising green process are unknown because of the special material removal mechanism of this process. This paper presents an analytical model for predicting SCE based on the material removal mechanism of whirling milling. The cutting parameters affecting the SCE characteristics are identified considering the un-deformed chip formation. An analytical model is developed as functions of the identified cutting parameters by calculating material removal volume and cutting forces. To validate the proposed model, the analytical model was applied in ball screw shaft whirling milling. The results indicate that the analytical model can be effectively used to predict the SCE with over 90% accuracy. In addition, the effects of cutting parameters and material removal rate (MRR) on SCE were investigated and analyzed based on the proposed model, which can provide valuable information and guidance for the optimal selection of cutting parameters to minimize SCE and improve MRR. Highlights: An analytical model for predicting specific cutting energy of whirling milling is proposed. Effects of cutting parameters and MRR on specific cutting energy of whirling milling are analyzed. The specific cutting energy characteristics based on material removal mechanism of whirling milling are investigated. The valuable information and guidance are obtained to minimize specific cutting energy and improve MRR.